2017
DOI: 10.1093/jamia/ocw160
|View full text |Cite
|
Sign up to set email alerts
|

Cost and economic benefit of clinical decision support systems for cardiovascular disease prevention: a community guide systematic review

Abstract: Objective This review evaluates costs and benefits associated with acquiring, implementing, and operating clinical decision support systems (CDSS) to prevent cardiovascular disease (CVD). Materials and Methods Methods developed for The Community Guide were used to review CDSS literature covering the period from January 1976 to October 2015. Twenty-one studies were identified for inclusion. Results It was difficult to draw a meaningful estimate for the cost of acquiring and operating CDSS to prevent CVD fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 29 publications
0
54
0
2
Order By: Relevance
“…110 Cost analysis is notoriously missing in the literature, but examples can be found. 107,111,112 Payers may be more willing to support CDSS if cost-savings can be shown elsewhere in the system / process. This means looking at more than just direct costs a using metrics such as patient outcomes or qualityadjusted life years (QALY).…”
Section: Financial Challengesmentioning
confidence: 99%
“…110 Cost analysis is notoriously missing in the literature, but examples can be found. 107,111,112 Payers may be more willing to support CDSS if cost-savings can be shown elsewhere in the system / process. This means looking at more than just direct costs a using metrics such as patient outcomes or qualityadjusted life years (QALY).…”
Section: Financial Challengesmentioning
confidence: 99%
“…[52] However, for future economic evaluations of EHR based CDS interventions, a more speci c approach for individual application areas or focus on medical risk factors is needed to draw meaningful conclusions from cost and outcome comparisons. [9] Moreover, decisionanalytic modelling techniques, e.g., Markov models, enable the evaluation of multiple income and outcome parameters. They address downstream costs or savings that may result from the introduction of health information technology.…”
Section: Discussionmentioning
confidence: 99%
“…During our search process, we found that the number of studies meeting the inclusion criteria increased tremendously in the past years, partially overlapping the present research question. [9][10][11] The most recent review by Jacob et al [9] examined the cost and economic bene ts of CDS systems restricted to cardiovascular disease prevention. However, the authors were unable to conclude whether these interventions were costbene cial or cost-effective.…”
Section: Table 1: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,4–7 According to Community Guide processes, since the Task Force recommended all five interventions based on evidence of their effectiveness, systematic economic reviews were subsequently completed. 3,5,8,9 …”
Section: Methodsmentioning
confidence: 99%